Estereotipos, homogenización e invisibilización en el imaginario de juventud propuesto por el relato publicitario - Acosta Martínez, Carolina Piedad; Palacios Chavarro, Janneth Arley (Folios, revista de la Facultad de Comunicaciones y Filología, 2022)
The aim of this article is to contrast the category of youth, known as traditionally instituted social imaginary, with the perspective of a group of university students, from their statements about a group of advertising commercials. The traditional social imaginary has tried to explain, to order and to control the youth, causing exclusion and segregation with respect to people located in that category. Results show that social imaginary has generated stereotypes, has tried to homogenize and invisibilize to youth people and that advertising had contributed to this situation through its statement. But also, findings evident certain resistance of the participants to this reduction and show their propositive role, distantly to the conception of passive and alienated consumer that the traditional critique has restored. Nevertheless, it does not stop considered to be the possibility that such a role should be promoted also by the statement itself as part of the advertising contemporary trends. Keywords: youth imaginary, advertising statement, youth, stereotypes, homogenization, invisibilization.